Dokumenty i sud'by . Dokumenty i sud'by . Documents and Destinies . Документы и судьбы - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Examination of archival documents telling the story of a Hungarian named Kulcsár, shot down in August 1944 over the Soviet Union, and was taken prisoner. Contributors: Mironenko, Sergei (Anchor) Рассмотрение архивных документов, рассказывающих историю венгра по фамилии Кулчар, сбитого в августе 1944 над территорией СССР и захваченного в плен. Создатели: Мироненко, Сергей (Ведущий/Ведущая)